Secondary malnutrition: clinico-etiological spectrum - Chandra, Surabhi; Singh, D. K. (International Journal of Contemporary Pediatrics, 2016)
Background:Secondary malnutrition, a less recognized entity results from an underlying disease that compromises growth directly or indirectly. The present study was undertaken to determine the clinico-etiological spectrum of secondary malnutrition in a tertiary care hospital of India. It also aimed at identifying asymptomatic masqueraders of malnutrition. Methods: In this prospective, observational study done in a tertiary care hospital over a year (April 2015 – March 2016), all patients admitted were evaluated anthropometrically, as per the World Health Organization (WHO) guidelines, and categorized into having moderate or severe malnutrition. Any underlying secondary cause was worked up and asymptomatic masqueraders were identified on the basis of a pre-devised fixed diagnostic protocol. Results:One seventy seven patients (177/897 = 19.7 %) of a total of 897 malnourished patients had secondary malnutrition. Seventy eight (78/177 = 44.0%) patients had moderate and 99 (99/177 = 55.9%) had severe malnutrition. Asymptomatic masqueraders of secondary malnutrition were seen in 21 patients. Neurological disorders (54/177 = 30.5%) followed by tropical infections (40/177 = 22.5%), were the major underlying cause of secondary malnutrition. Conclusions:Identification of secondary malnutrition and treatment of the underlying disorder is a must to achieve optimal nutritional outcomes and decrease the burden of malnutrition.